2018
DOI: 10.3390/su10082884
|View full text |Cite
|
Sign up to set email alerts
|

Ex-Ante Analysis of Economic, Social and Environmental Impacts of Large-Scale Renewable and Nuclear Energy Targets for Global Electricity Generation by 2030

Abstract: This study assesses the economic, social and environmental impacts of renewable and nuclear energy targets for global electricity generation by 2030. It examines different regions, as they might experience different impacts depending on the structures of their economies and their local natural resources, to understand the impact of these targets on their economics and well-being of their people. These regions are: Saudi Arabia, the United States (US), China, India, Europe and Rest of World (ROW). A well-known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 62 publications
(60 reference statements)
1
15
0
Order By: Relevance
“…Nevertheless, there are studies that have estimated the impact of renewable energy development on job creation to be negative, resulting in job losses. Almutairi et al (2018) show a loss of 4.45 million jobs worldwide up to 2030 in the Renewable and Nuclear Energy (RNE) scenario (based on the predictions of the international energy outlook) compared to the business as usual (BAU) scenario. This study (Almutairi et al, 2018) has made an effort to estimate both the direct and indirect jobs associated with the different energy scenarios by assessing the overall impacts on the gross domestic product (GDP) of different countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there are studies that have estimated the impact of renewable energy development on job creation to be negative, resulting in job losses. Almutairi et al (2018) show a loss of 4.45 million jobs worldwide up to 2030 in the Renewable and Nuclear Energy (RNE) scenario (based on the predictions of the international energy outlook) compared to the business as usual (BAU) scenario. This study (Almutairi et al, 2018) has made an effort to estimate both the direct and indirect jobs associated with the different energy scenarios by assessing the overall impacts on the gross domestic product (GDP) of different countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Almutairi et al (2018) show a loss of 4.45 million jobs worldwide up to 2030 in the Renewable and Nuclear Energy (RNE) scenario (based on the predictions of the international energy outlook) compared to the business as usual (BAU) scenario. This study (Almutairi et al, 2018) has made an effort to estimate both the direct and indirect jobs associated with the different energy scenarios by assessing the overall impacts on the gross domestic product (GDP) of different countries. However, Markandya et al (2016) found the net employment impacts from the transformation of the European Union energy sector in the period 1995-2009, when the European Union's energy structure went through a significant shift, away from the more carbon intensive sources, towards gas and renewables to be positive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, many studies argue against the "double dividend" effect of "green" policies, resulting in negative macroeconomic repercussions. For instance, Almutairi et al [58] evaluates the economic and societal implications of the implementation of the renewable and nuclear energy targets described in [59] for the cases of Saudi Arabia, United States of America, China, India, Europe, and the Rest of World (RoW) till 2030. To do so, they employ GTAP-E [60], an extension of the GTAP model [61] with energy specification, as described in [57].…”
Section: Relevant Workmentioning
confidence: 99%
“…Furthermore, Prăvălie and Bandoc (2018) emphasized that nuclear reactors are beneficial for decarbonization if nuclear waste management can be made properly, because long lived and weak waste management reactors will harm to environment. However, Almutairi, Thoma, and Durand-Morat (2018) established two scenarios as business as usual (BAU) and, RE and nuclear energy (RNE) by 2030. In RNE scenario, all countries' GDP rates and employment rates decreased without mitigating climate change except India.…”
Section: Literature Reviewmentioning
confidence: 99%